2006
DOI: 10.1158/1055-9965.epi-04-0822
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Mediators of a Nurse Intervention to Increase Skin Self-examination in Patients at High Risk for Melanoma

Abstract: This prospective study examines psychosocial mediators of an efficacious skin self-examination (SSE) intervention that includes provision of a whole-body digital photography book depicting the entire skin surface. Individuals (n = 100) with established risk factors for melanoma were recruited from the Memorial Sloan-Kettering Cancer Center Pigmented Lesion Clinic during their initial dermatologist visit and were randomized to receive a photobook immediately (n = 49) or 4 months after intervention delivery (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 26 publications
3
24
2
Order By: Relevance
“…Another study has shown that a feeling of taking effective action apparently reinforces adherence in performing skin self-examinations. 32 Our general practitioner-mediated intervention appeared generally safe and acceptable to patients. It is noteworthy, however, that the intervention patients tended to be more likely to worry about developing melanoma and to consult their practitioner again to discuss the disease.…”
Section: Key Findingsmentioning
confidence: 84%
See 1 more Smart Citation
“…Another study has shown that a feeling of taking effective action apparently reinforces adherence in performing skin self-examinations. 32 Our general practitioner-mediated intervention appeared generally safe and acceptable to patients. It is noteworthy, however, that the intervention patients tended to be more likely to worry about developing melanoma and to consult their practitioner again to discuss the disease.…”
Section: Key Findingsmentioning
confidence: 84%
“…19 The practitioners could give tailored advice on primary and secondary prevention, and adapt and personalize their counseling to the patient depending on the results of the clinical examination. Linking the counseling to the objective identification of lesions is an efficient and powerful strategy, [31][32][33][34] as general practitioners can perform 2 tasks simultaneously and possibly have greater influence than if they had simply given out written information. 21 Additionally, the practitioners can show patients which moles should be monitored and how to do it, improving patients' sense of self-efficacy.…”
Section: Key Findingsmentioning
confidence: 99%
“…Furthermore, these patients will be asked to take home a survey for their spouse, which mirrors the partner-related questions that the patient is asked to answer regarding SSE. Also at time 2, all study participants will receive a 20-minute standardized dermatological education on SSE derived from empirical evidence [14,29,47,50,65,98-104] and best practice guidelines [36,38,105-109]. Patients will be encouraged to attend the education session together with a significant other (e.g., spouse, other family member, friend) who could assist them with SSE.…”
Section: Method/designmentioning
confidence: 99%
“…The Skin Cancer Prevention Scale [122] captures whether patients performed SSE and have been advised by health care providers about SSE prior to their current melanoma diagnosis. The Skin Cancer Knowledge Scale, based on questionnaires by Hay et al 2006 [65] and Manne et al 2006 [45], assesses knowledge regarding melanoma risk, melanoma warning signs and SSE. The SSE Attitude Scale, an adaptation of Manne’s SSE Benefits and Barriers Scale [45], assesses perceptions of SSE importance, personal gain through SSE, and barriers to SSE.…”
Section: Method/designmentioning
confidence: 99%
See 1 more Smart Citation